Slope engineering for mountain roads - Hearn, G. J. (Geological Society, 2011)
This book provides a complete guide to the study, design, construction and management of landslide and slope engineering measures for mountain roads, with an emphasis on low-cost. The geographical focus of the book is on the tropics and sub-tropics, but is also highly relevant to other regions where heavy rain, steep slopes and weak soils and rocks combine to create slope instability. The causes and mechanisms of landslides are described, and the hazards they pose to mountain roads are illustrated. Methods of desk study, field mapping and ground investigation are reviewed and illustrated, with an emphasis on geomorphological and engineering geological techniques. The design and construction of alignments, earthworks, drainage, retaining structures, the stabilization of soil slopes and rock slopes, and the control of erosion on slopes and in rivers and streams are covered. Slope management as part of road maintenance and operation is reviewed, and procedures for risk assessment and works prioritization are described.
Keywords: Mountain roads -- Design and construction.; Slopes (Physical geography); elektronické knihy; electronic books